Diplomacy of the Sultanate of Ternate (1512 - 1607) - Yudistira, Rasyid Alif; Wijaya, Daya Negri (Universitas Islam Negeri Raden Intan Lampung, 2026)
This study focuses on the diplomacy of the Ternate Sultanate in the 16th century. Specifically, this study describes the Ternate-Portuguese alliance in political control and trade monopoly in the Maluku region. This study used historical methods to reconstruct and analyze 16th-century Ternate diplomacy. The method included heuristik, source criticism, interpretation, and historiography. The primary sources used were not only local sources such as the Hikayat Ternate but also Portuguese archives and chronicles such as Descobrimentos Antigo y Modernos by Antonio Galvao, as well as the Insulindia archive from Volumes 1 to 4, and used English and VOC archives as support.The results of the study show that Ternate diplomacy was pragmatic and adaptive, characterized by trade cooperation with the Portuguese to secure market access and military technology, while utilizing the relationship to consolidate internal power and suppress regional rivals such as Tidore. However, this diplomatic relationship also contained tensions due to excessive Portuguese political intervention. Following the collapse of this moral-based reciprocity, Ternate's diplomacy underwent a pragmatic shift during its interactions with the VOC in the 17th century. The Sultanate transitioned towards a highly legalistic and contractual diplomatic framework, actively utilizing formal treaties to dictate terms of military protection against the Spanish and to guarantee its sovereign survival. In conclusion, the diplomacy of the Sultanate of Ternate was not merely cooperative, but was a strategic instrument to maintain sovereignty, maximize economic benefits, and assert its hegemony as the center of political power in Maluku during the early days of European colonialism.